THE EFFECT OF USING GREEN FEEDSTUFFS SUPPLEMENTATION IN THE RATIONS OF LOCAL RABBITS ON SOME OF THEIR PRODUCTIVE CHARACTERS - ALI ABDUL-WAHAB MAHMOUD AL-KUHLA (Mesopotamia Journal of Agriculture)
The current work was carried out on fifteen multi-coloured male local rabbits aged 4-6 weeks old. The rabbits were allocated into three groups having a resembling mean live weights. The 1st group was fed a control ration composed of concentrated feed and fresh Lucerne (alfalfa) plants. The amount of lucerne used was represented by a quarter of the matter of the concentrated feed daily offered to the rabbits. The 2nd and the 3rd groups were fed conc. Feed as well as fresh celery and cabbage leaves for the other two groups, respectively. Throughout the feeding trial which lasted eight weeks total body gain and daily consumed feed were calculated. At the termination of the experiment, all rabbits were sacrificed and carcass measurements were taken. The findings showed that there was a significant difference (P≤0.05). between the 1st group as compared with the 2nd and 3rd groups in relation to total body weight. Also the results revealed that total concentrated feed a mount consumed was different among the three groups, with nearly similar feed conversion efficiency of all groups. There were a significant differences among the groups regarding mean hot carcass weights characters as well as fleshing percentages, considering dressing percentages and edible organ weights, there were no significant differences among the three groups. From the above results, It is advised not to add fresh celery or cabbage leaves alone to the concentrated rations of the local growing rabbits as a sole source of roughages because it may adversely affect their productive traits. therefore owing to the low crude fiber contents of celery and cabbage leaves, it is recommended to be mixed with other suitable roughages.